A review of visual SLAM for robotics: evolution, properties, and future applications - Al-Tawil, Basheer; Hempel, Thorsten; Abdelrahman, Ahmed; Al-Hamadi, Ayoub (Frontiers in Robotics and AI, 2024)
Visual Simultaneous Localization and Mapping (V-SLAM) plays a crucial role in the field of robotic systems, especially for interactive and collaborative mobile robots. The growing reliance on robotics has increased complexity in task execution in real-world applications. Consequently, several types of V-SLAM methods have been revealed to facilitate and streamline the functions of robots. This work aims to showcase the latest V-SLAM methodologies, offering clear selection criteria for researchers and developers to choose the right approach for their robotic applications. It chronologically presents the evolution of SLAM methods, highlighting key principles and providing comparative analyses between them. The paper focuses on integration of robotic ecosystem with Robotic Operating System (ROS) as Middleware, explores essential V-SLAM benchmark datasets, and presents demonstrative figures for each method's workflow.